Pengaruh Knowledge Sharing dan Kompetensi Terhadap Kinerja Karyawan di PT. PLN (Persero) Unit Pelaksana Pengendalian Pembangkit Bengkulu - M Naufal Arfan; Trisninawati Trisninawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of knowledge sharing and competence on employee performance at PT. PLN (Persero) UPDK Bengkulu. PT. PLN (Persero) UPDK Bengkulu is the implementing unit for controlling electricity generation in the Bengkulu region. The data in this study were collected using a questionnaire distributed to employees at PT. PLN (Persero) UPDK Bengkulu. In this study using 3 variables, namely knowledge sharing and competence as independent variables, while employee performance as the dependent variable. This research is expected to be a good evaluation and consideration for companies in improving employee performance. The results of this study found the influence of knowledge sharing and competence on employee performance. The results of this study are used as input for the company to find out how much influence knowledge sharing and competence has on employee performance so that the company can further improve employee performance in the future.